2019
DOI: 10.1016/j.jconrel.2018.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mucus is capable of stabilizing supersaturation of poorly water-soluble drugs

Abstract: The utilization of polymers to stabilize drug supersaturation and enhance oral drug absorption has recently garnered considerable interest. The potential role of intestinal mucus in stabilizing drug supersaturation, however, has not been previously explored. The ability for intestinal mucus to stabilize drug supersaturation and delay drug precipitation is potentially useful in enhancing the absorption of orally dosed compounds from drug delivery systems that generate supersaturation within the gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The good IVIVC obtained using the mucus-PVPA model (Fig. 4) together with the results described by Yeap and colleagues (Yeap et al, 2019) highlight the importance of having a mucus layer lining the permeation barrier when studying the permeation of supersaturated PWSD. This is especially relevant as the supersaturation stabilization process could be seen as an intrinsic mechanism of action for lipid-based formulations, and it should thus be taken into consideration in the development of novel drug delivery systems.…”
Section: Correlation With In Vitro Drug Permeationsupporting
confidence: 68%
See 3 more Smart Citations
“…The good IVIVC obtained using the mucus-PVPA model (Fig. 4) together with the results described by Yeap and colleagues (Yeap et al, 2019) highlight the importance of having a mucus layer lining the permeation barrier when studying the permeation of supersaturated PWSD. This is especially relevant as the supersaturation stabilization process could be seen as an intrinsic mechanism of action for lipid-based formulations, and it should thus be taken into consideration in the development of novel drug delivery systems.…”
Section: Correlation With In Vitro Drug Permeationsupporting
confidence: 68%
“…to play an important role in stabilizing drug supersaturation. In fact, it has been found that mucin and pig intestinal mucus were both able to delay precipitation during supersaturation-permeation experiments for two PWSD (Yeap et al, 2019). It has been proposed that the mechanisms enabling the stabilization of supersaturation exerted by the mucus layer were drug-specific.…”
Section: Correlation With In Vitro Drug Permeationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, rapid intestinal absorption reduces supersaturation and prevents rapid precipitation in the small intestine [ 94 , 95 , 96 ]. Furthermore, in vivo intestinal fluid components such as mucus can inhibit drug precipitation [ 97 ]. Taken together, in the case of free weak base drugs, it can be a good approximation to neglect particle growth and precipitation.…”
Section: Discussionmentioning
confidence: 99%